The Effect of Experiential Marketing on Revisit Intention at Mars Cafe Pomalaa in Kolaka Regency - Jingga Astri Ananta; Andry Stepahnie Titing; Hanif Kurniadi (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to analyze the effect of experiential marketing on customers’ revisit intention at Marz Cafe Pomalaa in Kolaka Regency. The study is motivated by the increasing importance of customer experience in shaping revisit intention, particularly in the café business, which offers not only food and beverages but also atmosphere, comfort, service quality, and social interaction space. Experiential marketing in this study is measured through five dimensions, namely sense, feel, think, act, and relate, while revisit intention is measured through customers’ willingness to revisit, invite others, share positive stories, and place Marz Cafe Pomalaa as a priority destination. This study employs a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 250 respondents selected using purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results indicate that all dimensions of experiential marketing have a positive and significant effect on revisit intention. The sense dimension is the most dominant factor in shaping customers’ revisit intention, followed by act, relate, think, and feel. The R-Square value of 0.717 indicates that the five dimensions of experiential marketing explain 71.7% of the variance in revisit intention, while the remaining percentage is explained by other variables outside the research model. These findings confirm that customer experiences involving sensory, emotional, cognitive, behavioral, and social aspects play an important role in encouraging customers to revisit. Practically, the management of Marz Cafe Pomalaa needs to maintain consistent taste quality, spatial design, atmospheric comfort, service speed, music suitability, and positive social interaction in order to strengthen customers’ revisit intention.